Integration of resistance exercise into a multimodal approach to prehabilitation for patients with sarcopenia prior to surgery: a narrative review - Patel, Harsh; Le, Khang Duy Ricky; Wang, Annie Jiao; Tay, Samuel Boon Ping (Frontiers in Rehabilitation Sciences, 2025)
IntroductionSarcopenia describes the process of progressive, generalised loss of skeletal muscle mass and strength, and has been recognised as a predictor of postoperative complications and mortality. Prehabilitation represents a clinical strategy where patients undergo both physical and psychological strategies in order to improve their functional capacity prior to surgery. Importantly, prehabilitation programs have been considered as an area of perioperative optimisation to address sarcopenia. However, the optimal prehabilitation program regimen remains poorly characterised. Instead of suggesting a novel prehabilitation strategy for sarcopenic patients, this review seeks to characterise the best-practice modalities and methods of resistance training as a component of multimodal prehabilitation to improve patient outcomes following surgery.MethodsA narrative review was performed following a search of Medline and Embase databases.ResultsThere is significant heterogeneity in the literature regarding best-practive resistance exercise regimens for patients with sarcopenia who are awaiting surgery. Overall, the literature highlights that programs with early involvement of clinicians, dietitians, nutritionists, and psychological support programs have been shown to improve patient outcomes compared to programs that did not. Additionally, asides from muscular hypertrophy, resistance exercise programs have been shown to have a multifactorial impact on sarcopenia, synergistically improving the domains of nutrition, mental health, hormonal imbalance, and chronic inflammation. The ideal approach to resistance exercise remains poorly understood, with a paucity of evidence surrounding the best methods for delivering such regimens. Despite this, key considerations revealed by this review include the need for prehabilitation clinicians to consider key aspects of resistance training including training volume, intensity with consideration into periodisation and progressive overload. Collaboration with multidisciplinary networks such as physiotherapists, exercise physiologists and personal trainers should be considered to ensure a safe and injury-free approach to resistance exercise in prehabilitation.ConclusionWhile there remains a lack of standardisation of prehabilitation protocols, the evidence suggests that multimodal prehabilitation should be considered in evidence-based frameworks to improve patient outcomes following surgery. In particular, the ability of resistance exercises to address multiple domains relevant to sarcopenia, thereby enhancing patient outcomes beyond pure hypertrophy and playing a key role in prehabilitation.